Experience of a TelEmergency program in Colombia South America: descriptive observational study between 2019 and 2021 (2023)
ABSTRACT: Introduction: Colombia has 50,912,429 inhabitants, but only 50-70% of the population can effectively access health care services. The emergency room (ER) is a main contributor to the in-hospital care system since up to half of the admissions come through it. Telemedicine has become a tool to facilitate effective access to health care services, improve the timeliness of care, reduce diagnostic variability, and reduce costs associated with health. The aim of this study is to describe the experience of a Distance Emergency Care Program through Telemedicine (TelEmergency) to improve specialist access for patients at the Emergency Room (ER) in low- and medium-level care hospitals in Colombia. Methods: An observational descriptive study of a cohort including 1,544 patients during the program's first two years was conducted. Descriptive statistics were used to analyze the available data. The data are presented with summarized statistics of sociodemographic, clinical, and patient-care variables. Results: The study included a total of 1,544 patients, and the majority were adults between 60 and 79 years of age (n = 491, 32%). More than half were men (n = 832, 54%), and 68% (n = 1,057) belonged to the contributory health care regime. The service was requested from 346 municipalities, 70% (n = 1,076) from intermediate and rural settings. The most common diagnoses were related to COVID-19 (n = 356, 22%), respiratory diseases (n = 217, 14%), and cardiovascular diseases (n = 162, 10%). We observed 44% (n = 681) of local admissions either under observation (n = 53, 3%) or hospitalization (n = 380, 24%), limiting the need for hospital transfers. Program operation data revealed that 50% (n = 799) of requests were answered within two hours by the medical staff. The initial diagnosis was modified in 7% (n = 119) of the patients after being evaluated by specialists at the TelEmergency program. Conclusions: This study shows the operational data collected during the first two years after the implementation of the TelEmergency program in Colombia, the first of its kind in the country. Its implementation offered specialized timely management of patients at the ER in low- and medium-level care hospitals, where there is no availability of specialized doctors.